Mucin histochemistry of stomach in metaplasia and adenocarcinoma: An observation - Mandal, Prakas Kumar; Chakrabarti, Sudipta; Ray, Amit; Chattopadhyay, Bitan; Das, Shikha (Indian Journal of Medical and Paediatric Oncology, 2013)
Background: There is a variable pattern of occurrence of gastric carcinomas world-wide, partially reflecting the frequency of various changes of gastric mucosa from, which such neoplasm occur. Many cases of gastric carcinoma originate in the background of chronic gastritis caused by Helicobacter pylori. Subsequent intestinal metaplasia (IM) can be morphologically classified by routine and special histopathological stains. Materials and Methods: The present study was conducted over the 2 years at NRSMC & H, Kolkata. Aims of the present study were to search for evidences of H. pylori infection, classification of different metaplastic and/or malignant changes, identification of types of mucin by mucin histochemistry and their interrelationship in gastrectomy and gastric biopsy specimens (total 70). After obtaining clinical history, radiological and endoscopic findings were noted. After macroscopic study of the specimen, hematoxylene and eosin, southgate mucicarmine, periodic acid schiff-alcian blue (PAS-AB) and gomori aldehyde fuchsin (GAF)/AB staining were performed to classify gastric carcinoma and metaplastic changes and to correlate with staining patterns of mucin. Results: The overall male to female ratio was 2.89:1. Age ranged from 22 years to 78 years and the commonest age group of gastric carcinomas being 41-50 years (26 cases, 37.1%). Gastric adenocarcinoma was found in 61 (87.1%) cases (22.9% were of intestinal type and 77.1% of diffuse type) and only IM was found in 9 (12.9%) cases. Overall the rapid urease test was positive in 18 (25.7%) cases majority of which showing either pure IM or IM associated with intestinal type of gastric carcinoma. All diffuse types of gastric carcinoma (47 cases, 77.1%) were showed PAS positive staining (indicating neutral mucin) whereas in 15 (65.2%) cases of IM columnar cells stained with AB (representing acidic mucin). GAF/AB stain revealed Type II IM in 10 (43.5%) cases and Type III IM in 4 (17.4%) cases. Conclusion: Routine and special histological staining is particularly useful for histological subtyping of gastric carcinomas and IMs.
Keywords: Gastric carcinoma; histochemistry; intestinal metaplasia of stomach; mucin stain